Fixed assets-infrastructure and financial health in hospitality industry: A chaotic effect in emerging markets (2014)
The influence of property, plant and equipment (Fixed Assets) and the quality of infrastructure on return was analyzed in the hospitality industry in emerging markets. The analysis unit was Colombia, a member of the CIVETS emerging market group. Financial healthwas determined by the relationships among return on fixed assets ratio,fixed assets net worth and fixed assets turnover ratios. Besides, the degree of accomplishment of the government plans to improve the quality of infrastructure was considered an indicator of an adequate infrastructure. Transformation by Hénon map equations were applied to data and a recurrence plot, phase space and recurrence quantification analysis were obtained. It was determined the influence of fixed assets net worth and turnoveron the return on fixed assets, and then, the influence of infrastructures on return on fixed assets. A non-linear, non-monotonic relationship existedamongreturn on fixed assets, fixed assets net worth and fixed assets turnover ratios, making investment decision difficult. An adequate development of infrastructure tended to relax the parameters of recurrence, slightly promoting a more steady development of the firms.